Material Properties of Lime Mortars Used in the Architectural Heritage of the Joseon Dynasty - Han Ul Im; Sang Ok Lee; Gwang Yong Chung (Heritage)
This study aimed to identify the raw materials and characteristics of lime mortar samples recovered from three Joseon dynasty architectural heritage sites: the Munsusanseong Fortress in Gimpo, Namhansanseong Fortress, and Godeung-dong lime-barrier tomb in Seongnam. To achieve this, comprehensive analyses were conducted, including physical property assessments (specific gravity, water absorption, apparent porosity, hydrochloric acid aggregate test, and particle size distribution), material characterization using optical microscopy and SEM-EDS, as well as XRD, WD-XRF, and TGA analyses. The results revealed that the lime mortars from all three sites exhibit the characteristics of Sammulhoe, a traditional Joseon dynasty mixture of lime, sand, and clay minerals. While the binders primarily consisted of air-setting lime, minor hydraulic properties were observed in the samples from the Namhansanseong Fortress and the Godeung-dong lime-barrier tomb, possibly due to the inclusion of dolomite. Additionally, the presence of brick and tile particles (Waseol) in some samples corroborate historical records of lime mortar production techniques during the Joseon dynasty. This study provides scientific insights into the raw materials and characteristics of the Joseon dynasty lime mortar, contributing to a deeper understanding of traditional construction materials and techniques.